Invitro Bio-Assay of Some Botanicals Against Some Important Soil-Borne Fungi - Timila, Ram D.; Manandhar, S. (Journal of the Plant Protection Society, 2018)
Sclerotinia sclerotiorum causing white mold disease, Fusarium solani and Rhizoctonia solani causing root rot/wilt complex and Sclerotium rolfsii causing collar rot are economically important soil-borne pathogens of various crops having wide host range. Eight different botanical extracts were evaluated for their antifungal effects against the four above-mentioned fungi under laboratory conditions using food poison technique. Five percent crude extracts of garlic clove (Allium sativum), rhizome of bojo (Acorus calamus), leaves of castor (Ricinus communis), asuro (Justicia adhatoda), sambucus (Sambucus hookeri), neem (Azadirachta indica), bougainvillea (Bougainvillea glabra), and dried fruits of timur/Sichuan pepper (Zanthoxylum armatum) were included in the experiment. Three PDA plates for each treatment were inoculated with each pathogen and incubated at room temperature (24-25°C). Efficacy of the treatments on inhibition of radial growth of the pathogen colony was assessed 96 hours (4 days) after inoculation and compared with control without botanical extract. Significant inhibitory effect on radial growth of S. sclerotiorum was found with garlic (70% inhibition) followed by sambucus (22%) and asuro (12%). It was also observed that asuro treated plates had least sclerotia formation of the pathogen followed by sambucus. Bojo was found effective in inhibiting the radial growth of R. solani by 14% and S. rolfsii by 54% whereas, castor extract was found effective against F. solani with 21% inhibition in colony growth. Hence, these botanicals could have the potential in managing the diseases incited by the test pathogens, however, firstly their efficacy in the field conditions needs to be verified.